2007
DOI: 10.1097/wco.0b013e3282f1a043
|View full text |Cite
|
Sign up to set email alerts
|

Cranial base approaches to inaccessible intracranial tumors

Abstract: Operative trajectories created through the cranial base, although technically demanding, have led to substantially improved outcomes for a wide variety of inaccessible intracranial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Its application in various skull base procedures, either as a sole visualizing tool or as an adjunct to the microscope, is constantly expanding [1]. The endoscope provides superior illumination and magnification, as well as possibility "to look around the corner", thus allowing for more radical but safe surgeries [2].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Its application in various skull base procedures, either as a sole visualizing tool or as an adjunct to the microscope, is constantly expanding [1]. The endoscope provides superior illumination and magnification, as well as possibility "to look around the corner", thus allowing for more radical but safe surgeries [2].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…In present endoscopic surgery instruments must avoid vital vessels and avert damage to tissue around the wound. 58,59) Here we choose the 0.7 mm needle, which is close to the mainstream diameter endoscope adopt by clinical surgery 60) and we did not observe any side-effect conditions, such as haemorrhage and death. Previous studies suggested that all kinds of trauma could influence neural function in a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, the patterns of recurrence included local (78%), surgical pathway seeding (5%), regional nodal (3%) and/or metastases (20%). Total or near-total resection is accepted as being an important factor for local control of chordomas; however, the aggressive surgical treatment has sometimes been associated with increased patient morbidity and mortality rates [7][8][9] resulting in lower quality of life for survivors. 10 Therefore, the combination of maximal surgical resection within a safe range and optimal post-operative radiotherapy is very important for preventing local tumour recurrence and maintaining patients' performance status (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4 Although the surgical removal of skull base chordomas remains the mainstay of treatment, complete removal is often difficult because of the location 1,5,6 and aggressive surgical treatment has sometimes been associated with increased patient morbidity and mortality. [7][8][9] Patients with a skull base chordoma who underwent surgery and/or radiotherapy were reported to have a lower quality of life than normal population mainly because of neurological deficits. 10 In addition, even if gross total removal is achieved, the local recurrence rate is high because of common infiltration to the surrounding bony tissue along the lines of least resistance.…”
Section: Introductionmentioning
confidence: 99%